Drivers of IPM Adoption among Hybrid Tomato Farmers in Karnataka: Insights through mlogit Model - Lal, Sudhanand Prasad; K. N..Sunil Kumar ,; Gyan Shukla, (Indian Journal of Extension Education, 2025)
The investigation was undertaken during 2020 to study the adoption level of IPM practices and the factors influencing adoption among hybrid tomato growers in Karnataka as such studies are scanty in India despite 60% market share of hybrid tomato. Primary data were collected using a structured interview schedule by personally interviewing 120 respondents. Findings revealed that cultural practices like crop rotation, exhibited higher adoption rates, while biological methods were relatively less adopted. Overall, IPM adoption remained limited, with only a small proportion of growers fully embracing these practices. Multinomial logistic regression (MLR) had Nagelkerke’s R-square or Pseudo R2 value of 0.609, indicating 60.90% of total variations in the adoption level of IPM practices, explained by selected explanatory variables. Further, MLR identified factors significantly influencing the adoption of IPM were age (p=0.021), education (p=0.022), social contact (p=0.013), and cosmopoliteness (p=0.29) (odds ratio [OR], 6.707; 95% CI of OR 1.211 to 37.158) found significant at 5% level (p